(untitled) (The International Journal for Scientific Research, 2023)
The importance of the topic lies in knocking on the door of a few of its ways and trying to open its closures and explain its origins, and the danger of entering this door without knowledge, and in some of it is a fabrication against the Book of God that needs responses; The objectives of the research will be to clarify the foundations and rules governing this science, to differentiate between acceptable and rejected in this section and to explain their reasons, and to respond to those who opened this door wide. Synonymous and does it exist in the language and in the Qur’an? And if there is, is it necessary for synonyms to fully match the meaning? And if it does not mean a complete match, then how do you control the linguistic differences in the meanings of synonyms? The most important results came in a statement that synonymy is one of the linguistic phenomena of high importance and lofty rhetoric in the Arabic language. Where the meaning - in most cases - exceeds the meaning of other words, and the origin of words is that they are not synonymous, especially in the Holy Qur’an. Weakness prevails over what some contemporaries alone used in differentiating between the meanings of Quranic synonyms.